The influence of a STEM unit on the interest in and understanding of science and engineering between elementary school girls and boys - Tracy Hewitt; Frank Forcino (Discover Education)
Abstract Integrating hands-on Science, Technology, Engineering, and Math (STEM) education with a focus on the engineering design process into elementary school curricula has been associated with positive outcomes, including enhanced student understanding and increased interest in the topics. Here, we evaluated third grade student interest and perceived knowledge before and after a STEM unit on roller coasters and engineering was taught in this mixed-methods study. Pre and post instructional survey responses were compared and case studies were developed to determine student interest in and perceived understanding of STEM subjects, specifically science and engineering, before and after the unit. The study explores gender differences among students, aiming to identify variations in the impact of the STEM unit on boy and girl students. Prior to engaging in this unit, boys demonstrated higher interest in science and engineering than girl students. Post-unit, girls increased their interest in science and engineering at a higher rate than their boy counterparts. Students self-reported gaining knowledge about STEM subjects as a result of their participation in this unit. These findings were substantiated through the analysis of pre- and post-unit surveys as well as detailed case studies conducted on six students participating in the instructional unit. This study demonstrates the positive impact of engaging in a STEM unit on elementary school students’ interest in and knowledge of STEM subjects such as science and engineering. The findings underscore the importance of introducing STEM concepts at the elementary school level. Girl participants demonstrated an increase in interest at a higher rate than their boy peers, demonstrating the importance of teaching girls STEM from a young age. Therefore, teaching STEM and engineering units to elementary school students can have a strong impact on both girl and boy interest in and understanding of science and engineering.